Aelred z Rievaulx, Pewien wspaniały cud - Groń, Ryszard Stefan; Dutton, Marsha L.; Sochań, Robert (Vox Patrum, 2024)
The aim of the article is to present a translation from ecclesiastical Latin into Polish together with a commentary on the work of the 12th-century English abbot from the Cistercian abbey in Rievaulx, Aelred, entitled A Certain Wonderful Miracle. The article is divided into three parts: a short note on the life and work of Aelred (1110-1167), his literary legacy, including its translations into Polish (1); presentation of the work itself, taking into account its environment, history, meaning and purpose (2). The first part is written by the editor of this project, Ryszard Groń; the second part was written by prof. Marsha L. Dutton, from the Ohio University in the USA, invited to cooperate. The translation from Latin was undertaken by Robert Sochań, the translation of the article by prof. Dutton from English was made by Ryszard Groń. The third part is the Polish text of the presented work by Aelred (3).